1987
DOI: 10.1007/bf00199157
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alfa corrects thrombocytosis in patients with myeloproliferative disorders

Abstract: During previous therapeutic trials with interferon, decreased levels of peripheral platelet counts have been observed. Taking advantage of this effect, we investigated the efficacy of recombinant interferon (rec-IFN) in the treatment of thrombocytosis in myeloproliferative diseases. A total of 15 patients with polycythemia vera, essential thrombocytosis, or chronic myeloid leukemia received rec-IFN-alfa at initial doses of 25-70 x 10(6) units/week; maintenance therapy following week 8 of treatment consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 31 publications
(25 reference statements)
3
20
0
Order By: Relevance
“…Already in 1985, Linkesch et al from Austria described that IFN-alpha2 was able to control myeloproliferation in myeloproliferative diseases with severe thrombocytosis [53, 54]. Since then, several studies during the last 30 years have subsequently confirmed that IFN-alpha2 is also able to inhibit myeloproliferation in the Philadelphia-negative MPNs with a reduction or alleviation of the need of phlebotomies in PV, disappearance of pruritus, normalization of elevated leucocyte and platelet counts, and a reduction in spleen size [1950, 5559].…”
Section: History Of Ifns In Mpnsmentioning
confidence: 99%
“…Already in 1985, Linkesch et al from Austria described that IFN-alpha2 was able to control myeloproliferation in myeloproliferative diseases with severe thrombocytosis [53, 54]. Since then, several studies during the last 30 years have subsequently confirmed that IFN-alpha2 is also able to inhibit myeloproliferation in the Philadelphia-negative MPNs with a reduction or alleviation of the need of phlebotomies in PV, disappearance of pruritus, normalization of elevated leucocyte and platelet counts, and a reduction in spleen size [1950, 5559].…”
Section: History Of Ifns In Mpnsmentioning
confidence: 99%
“…[12][13][14][15] Some case reports have shown that IFN can cause normalization of chromosomal abnormalities in PV. 16,17 Lengfelder et al summarized treatment results with IFN in 279 patients with PV and 273 patients with ET.…”
mentioning
confidence: 99%
“…IFN-a has been reported to be beneficial in treating myeloproliferative disorders, such as chronic myelogenous leukemia (CML) [23,24], essential thrombocytosis, and polycythemia Vera [25]. IFN-a has also been reported to be effective in treating fibrosis conditions, such as scleroderma [26], possibly through its effect of inhibiting collagen synthesis by dermal fibroblasts [27].…”
Section: Discussionmentioning
confidence: 99%